USING ACTIVITY-BASED APPROACH TOOLS in the work of after-school care groups IN PRIMARY SCHOOLS - Groshovenko, Olga; Prysiazhniuk, Larysa (Mountain School of Ukrainian Carpaty, 2024)
This article explores the application of activity-based approach tools in the work of extended day groups (EDG) in primary schools. The activity-based approach, a modern educational methodology, prioritizes students' active participation in acquiring knowledge, developing skills, and forming key competencies. The study highlights the integration of educational, developmental, and instructional components within EDG activities through the use of this approach, creating favorable conditions for the harmonious development of young learners. The authors analyze contemporary tools of the activity-based approach that can be effectively incorporated into EDG practices, such as interactive teaching methods, project-based learning, integrated lessons, creative workshops, and gamebased technologies. The article provides specific examples of their application across various activities, including organizing independent study sessions, facilitating creative tasks, and conducting extracurricular events. Key advantages of the activitybased approach are outlined, including the promotion of cognitive engagement, the cultivation of critical thinking, increased learning motivation, and the development of students’ social and emotional competencies. The article emphasizes the importance of tailoring teaching methods to the individual needs and abilities of students, as well as the pivotal role of the teacher-coordinator in organizing EDG activities. The practical recommendations and methodological approaches proposed in this study can be utilized by educators to enhance the efficiency and effectiveness of extended day group operations in primary schools.